Programmable Hydrogel Ionic Circuits for Biologically Matched Electronic Interfaces. Issue 25 (2nd May 2018) - Zhao, Siwei; Tseng, Peter; Grasman, Jonathan; Wang, Yu; Li, Wenyi; Napier, Bradley; Yavuz, Burcin; Chen, Ying; Howell, Laurel; Rincon, Javier; Omenetto, Fiorenzo G.; Kaplan, David L.
Abstract: The increased need for wearable and implantable medical devices has driven the demand for electronics that interface with living systems. Current bioelectronic systems have not fully resolved mismatches between engineered circuits and biological systems, including the resulting pain and damage to biological tissues. Here, salt/poly(ethylene glycol) (PEG) aqueous two‐phase systems are utilized to generate programmable hydrogel ionic circuits. High‐conductivity salt‐solution patterns are stably encapsulated within PEG hydrogel matrices using salt/PEG phase separation, which route ionic current with high resolution and enable localized delivery of electrical stimulation. This strategy allows designer electronics that match biological systems, including transparency, stretchability, complete aqueous‐based connective interface, distribution of ionic electrical signals between engineered and biological systems, and avoidance of tissue damage from electrical stimulation. The potential of such systems is demonstrated by generating light‐emitting diode (LED)‐based displays, skin‐mounted electronics, and stimulators that deliver localized current to in vitro neuron cultures and muscles in vivo with reduced adverse effects. Such electronic platforms may form the basis of future biointegrated electronic systems. Abstract : Programmable hydrogel ionic circuits completely composed of salt, water, and biofriendly hydrogels are developed based on salt/poly(ethylene glycol) aqueous two‐phase systems. Such systems enable designer electronics that match the properties of biological systems and route high‐resolution ionic electrical signals between engineered and living systems while avoiding tissue damage. Such platforms may form the basis of future biointegrated electronic systems.